Ex vivo oral biofilm model for rapid screening of antimicrobial agents including natural cranberry polyphenols - Guy R. Adami; Wei Li; Stefan J. Green; Elissa M. Kim; Christine D. Wu (Scientific Reports)
Abstract The search has been ongoing for safe and effective antimicrobial agents for control and prevention of oral biofilm associated with disease. Clinical trials for oral specific anti-bacterials are costly and often provide inconclusive results. The simple approach of ex vivo testing of these agents has not demonstrated utility, likely due to variability of effects observed even with a single donor. We show how shed oral biofilms, easily obtained from donor saliva, and tested under optimized conditions, respond reproducibly to anti-bacterial challenges measured by reductions in rRNA accumulation in susceptible taxa. Responses are in part donor specific, but many bacteria taxa were shown to be reproducibly susceptible over a group of donors. For two antibiotics, vancomycin and penicillin G tested at pharmacologic levels, a subset of Gram-positive bacteria was inhibited. A natural product with antibacterial properties, diluted Vaccinium macrocarpon (cranberry) juice, was shown to inhibit a range of oral taxa, including Alloprevotella sp__HMT_473, Granulicatella adiacens, Lachnoanaerobaculum umeaense, Lepotrichia sp__HMT_215, Peptostreptococcus stomatis, Prevotella nanceiensis, Stomatobaculum sp__HMT_097, Veillonella parvula, and kill some targets. The model discussed in this study has promise as a rapid, precise, and reproducible ex vivo method to test and identify potential clinically useful antimicrobial agents active against the oral biofilm community.